Effects of different levels of preharvest shading on the storage quality of strawberry (Fragariax ananassaDuchesne) cv. Ostara II. chemical characteristics - Osman, Azizah; Peter B., Dodd (Universiti Putra Malaysia Press, 1994)
To study the effects of different levels of preharvest shading (74, 58, 48, 38 and 5% of light penetration which were denoted by So' SI' S2' 53 and S4 respectively) on developing strawberry (Fragaria X ananassa Duchesne) cv. Ostara fruits, some chemical tests (pH, total soluble solids and titratable acidity) associated with fruit quality were carried out. Results showed that although the different levels of preharvest shading were found to demonstrate a significant effect on the chemical parameters studied, this could only be detected in fruits shaded by S4 and S3. However, for total soluble solids, significant interactions were observed between location of fruit and fruit type and also between storage day and fruit type.